Effect of endophytic entomopathogenic fungal conidia and blastospores induced in maize plants by seed inoculation on Spodoptera frugiperda immune response and mortality - JELLY MILINIA PUSPITA SARI; SITI HERLINDA; SUWANDI SUWANDI; ELFITA ELFITA (Society for Indonesian Biodiversity, 2023)
Abstract. Sari JMP, Herlinda S, Suwandi S, Elfita. 2023. Effect of endophytic entomopathogenic fungal conidia and blastospores induced in maize plants by seed inoculation on Spodoptera frugiperda immune response and mortality. Biodiversitas 24: 5709-5717. Endophytic entomopathogenic fungi (EPF) can produce conidia and blastospores; however, the pathogenicity of conidia and blastospores inoculated in plants on Spodoptera frugiperda larvae is limited. This research aimed to detect the effect of the endophytic entomopathogenic fungal conidia and blastospores induced in maize plants by seed inoculation on S. frugiperda's immune response and mortality. A total of 10 isolates of endophytic EPF were used in this experiment. The study revealed that 9 days after treatments, S. frugiperda larvae consuming maize leaves inoculated with blastospores of endophytic entomopathogenic fungi; their hemocyte concentration did not show any significant differences between the fungal treatments and control. However, 1 up to 7 days after treatments, the concentration significantly differed from the control. Furthermore, B. bassiana JgSPK, JaGiP, and JaSpkPGA(2) isolates tended to be the most pathogenic compared to other isolates. Feeding on leaves colonized by endophytic EPF could reduce the larval and pupal weight of S. frugiperda. The percentage of S. frugiperda non-emergence pupae from larvae-eating maize leaves colonized with B. bassiana JgSPK and JaGiP isolates was significantly higher than other fungal treatments and the control. The endophytic entomopathogenic fungal conidia and blastospores inoculated in maize plants by seed inoculation have a lethal effect on S. frugiperda larvae. However, exposure to conidia and blastospores did not reduce or increase the hemocyte concentration in the larvae hemolymph of S. frugiperda.